2004
DOI: 10.1158/0008-5472.can-03-1476
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Reduction and Transcriptional Up-Regulation of Glucosylceramide Synthase through Doxorubicin-Activated Sp1 in Drug-Resistant HL-60/ADR Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Glycosphingolipids, produced by ceramide glycosylation, upregulate MDR1 expression via cSrc signaling and TCF4/b-catenin recruitment (29). Increased GCS and P-gp expression in response to anticancer drugs confers cancer cell resistance by augmenting ceramide glycosylation and MDR1-mediated drug efflux (24,30). Furthermore, GCS silencing, achieved by transfection of GCS siRNA or mixed-backbone oligonucleotides, delays the clearance of ceramide generated in response to chemotherapeutic drugs and reverses cell resistance by suppression of MDR1 (18,31).…”
Section: Discussionmentioning
confidence: 99%
“…Glycosphingolipids, produced by ceramide glycosylation, upregulate MDR1 expression via cSrc signaling and TCF4/b-catenin recruitment (29). Increased GCS and P-gp expression in response to anticancer drugs confers cancer cell resistance by augmenting ceramide glycosylation and MDR1-mediated drug efflux (24,30). Furthermore, GCS silencing, achieved by transfection of GCS siRNA or mixed-backbone oligonucleotides, delays the clearance of ceramide generated in response to chemotherapeutic drugs and reverses cell resistance by suppression of MDR1 (18,31).…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by numerous cell-based and animal studies showing the ability of ceramide to induce cell cycle arrest or apoptosis (9)(10)(11). Furthermore, ceramide has been shown to function as a key mediator of apoptosis brought on by stress-inducing therapeutic agents, such as anthracyclines (11)(12)(13)(14), ionizing radiation (15,16), tumor necrosis factor (TNF)-related apoptosis-inducing ligand (17), and paclitaxel (18). Reciprocally, the inhibition of ceramide production by compounds such as the ceramide synthase inhibitor fumonisin B1 or by small interfering RNA approaches has been shown to abrogate stress-induced apoptosis (11,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of ceramide levels (a) by stress-inducing agents (11)(12)(13)(14)(15)(16)(17)(18) or (b) as noted in multiple primary tumor types (reviewed in refs. 3,22) is likely to result due to multiple changes in the regulation of ceramide-metabolizing enzymes or pathways; however, the exact molecular mechanisms responsible for these alterations remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed the importance of GCS in the mechanism of cancer drug resistance. Further studies demonstrated that a GC-rich/Sp1 promoter binding region was of importance in the regulation of GCS expression and doxorubicin could induce activation of Sp1 and up-regulation of GCS and apoptosis in Leukimia drug-resistance cell line HL-60/ADR and ovarian cell line NCI/ADR-RES [81,90]. In 2009, Eugen Ruckhäberle et al analyzed microarray data of GCS expression in 1,681 breast tumors and found that expression of GCS was associated with a positive estrogen receptor (ER) status, lower histological grading, low Ki67 levels and ErbB2 negativity (P < 0.001 for all) [91].…”
Section: Glucosylceramide Synthasementioning
confidence: 99%
“…So it is easily to understand that increased ceramide has been oberserved in response to many anti-cancer drugs, such as doxorubicin, vincristine, paclitaxel, etoposide, PSC 833 and fenretinide. Many enzymes have been confirmed to be responsible for the regulation of ceramide levels, such as ceramide synthase and sphingomyelinase which are responsible for the ceramide generation, and sphingomyelin synthase and ceramidase which take part in the ceramide metabolization [81]. Glucosylceramide synthase (GCS) is one of them.…”
Section: Glucosylceramide Synthasementioning
confidence: 99%